Educational Financing Management Strategy in Improving the Quality of School Services - Suwarni; Jumiati Siska; Feby Elra Perdima; Aurelio Jr., S. Gomez (The Indonesian Institute of Science and Technology Research, 2026)
This study examines educational financing management strategies and their impact on the quality of school services at MTs Negeri 2 Bengkulu Tengah, an Islamic junior secondary school in Indonesia. Employing a qualitative case study design, data were collected through semi-structured interviews with the principal, treasurer, teachers, and school committee members, supported by non-participant observations and analysis of financial and planning documents, including the School Activity and Budget Plan (Rencana Kegiatan dan Anggaran Sekolah or RKAS) and School Operational Assistance (Bantuan Operasional Sekolah or BOS) realization reports. Data triangulation was applied to enhance credibility and analytical rigor. The findings reveal that the madrasah implements a strategic financing model characterized by participatory budget planning, priority-based allocation, transparent financial reporting, and multi-layered monitoring involving internal and external oversight. Empirical evidence demonstrates measurable impacts in three domains: (1) improvement of facilities and Information and Communication Technology (ICT) supported learning environments, (2) enhancement of teacher professional and digital competencies through targeted training allocation, and (3) strengthening of student services reflected in increased extracurricular participation and reduced absenteeism rates. Financial transparency and stakeholder engagement further contribute to strengthened public trust and institutional accountability. This study contributes to educational management scholarship by presenting an evidence-based financing governance model integrating strategic planning, participatory decision-making, and continuous evaluation. The findings highlight that the effectiveness of educational financing depends not merely on the availability of funds but on strategic, transparent, and accountable management practices that align financial decisions with service quality improvement objectives.